Renewal Analysis of Islamic Stock Criteria in Indonesia - Prasetyo, Yoyok; Aen, Nurol; Hakim, Sofyan Al; Perwira, Mohammad Bagus Teguh; Sukmarini, Dien (Madania: Jurnal Kajian Keislaman, 2019)
Muslim is the majority population in Indonesia. This has become a background to provide investment instruments to meet Islamic principles. This study analyzes the renewal of Islamic stock criteria established through Bapepam LK (The Financial Services Authority/OJK) regulations. This is normative juridical research, with the object of Bapepam LK Regulations regarding Islamic stock criteria. In Indonesia, the Islamic stock criteria were first established in 2007. Bapepam LK then made an update on the Islamic stock criteria in 2009, and the last update was in 2012. Updates in 2009 were carried out on qualitative criteria, while the quantitative criteria remained. This renewal made the criteria for Islamic stocks more stringent. While the renewal in 2012 was carried out on quantitative criteria, the qualitative criteria remained steady. This renewal had eased the criteria for Islamic stock. The results of the study showed that the issuance and renewal for the Islamic stock criteria was carried out by Bapepam LK based on the fatwa and approval letter of National Sharia Council (DSN) of Indonesian Ulema Council (MUI). The stipulation of the criteria for Islamic stocks is the outcome of DSN MUI’s ijtihad Negara Indonesia memiliki jumlah penduduknya muslim yang besar. Hal ini menjadi pendorong untuk menyediakan instrumen investasi berupa saham yang memenuhi kriteria syariat Islam. Penelitian ini menganalisa pembaharuan kriteria saham syariah yang ditetapkan melalui Perauran Bapepam LK (Sekarang OJK). Penelitian ini bersifat yuridis normatif, dengan objek Peraturan Bapepam LK tentang kriteria saham syariah. Di Indonesia, kriteria saham syariah ditetapkan pertama kali pada tahun 2007. Kemudian  Bapepam LK  melakukan pembaharuan dalam kriteria saham syariah pada tahun 2009. Dan terakhir pembaharuan dilakukan pada tahun 2012. Pembaharuan pada tahun 2009 dilakukan pada kriteria kualitatif, adapun kriteria kuantitatif tetap. Pembaharuan ini menyebabkan kriteria saham syariah semakin ketat. Sedangkan pembaharuan pada tahun 2012 dilakukan pada kriteria kuantitatif, adapun kriteria kualitatif tetap. Pembaharuan ini menyebabkan kriteria saham syariah mengalami pelonggaran. Hasil kajian menunjukan bahwa penerbitan dan pembaharuan demi pembaharuan kriteria saham syariah dilakukan Bapepam LK bersumber pada fatwa dan surat persetujuan Dewan Syariah Nasional (DSN) Majelis Ulama Indonesia (MUI). Penentuan dalam kriteria saham syariah merupakan hasil ijtihad DSN MUI.